REFLEKSI KULTURAL DAN PENDIDIKAN KARAKTER DALAM TRADISI RUWAHAN DI DUSUN URUNG URUNG - Doni Uji Windiatmoko; Asih Andriyati Mardliyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe the procession or Ruwah Urung Urung ritual and the value of local wisdom and reflection on character education contained in the tradition. The method used is descriptive qualitative with ethnographic approach. Sources of data and research data are cultural phenomena of society. The technique of collecting data is by observation and in-depth interviews. Data analysis with interactive analysis methods. The results showed that the Hamlet Ruwah ritual was held in each RT, the Bancakan tradition contained cone, porridge, fine white chicken, and others. There is a value of local wisdom, namely how to get along well, maintain culture/ culture, culture and religion. Regarding the reflection of character education, there are eight character values ??contained in the Ruwah ritual, namely religious, creative, independent, communicative, happy to be friendly and proactive, love peace, care for the environment, social care, and responsibility. Keywords: Hamlet Ruwah, Local Wisdom, Character education